Campylobacter coli From Retail Liver and Meat Products Is More Aerotolerant Than Campylobacter jejuni - Karki, Anand B.; Marasini, Daya; Oakey, Clark K.; Mar, Kaitlin; Fakhr, Mohamed K. (Frontiers in Microbiology, 2018)
Aerotolerance in the microaerophilic species Campylobacter was previously reported and could increase bacterial survival and transmission in foods during stressful processing and storage conditions. In this study, 167 Campylobacter isolates (76 C. jejuni and 91 C. coli) were screened for aerotolerance; these strains were previously isolated from retail chicken meat, chicken livers, chicken gizzards, turkey, pork, and beef liver samples. Bacterial cultures were incubated aerobically in Mueller Hinton broth with agitation and viable cell counts were taken at 0, 6, 12, and 24 h. Approximately 47% of the screened Campylobacter isolates were aerotolerant (viable after a 12-h aerobic incubation period), whereas 24% were hyper-aerotolerant (viable after a 24-h aerobic incubation). A greater prevalence of aerotolerant strains (80%) was found among C. coli isolates as compared to C. jejuni isolates (6%). Differences in the oxidative stress response related genes were detected among C. jejuni and C. coli isolates when comparative genomics was used to analyze 17 Whole Genome Sequenced (WGS) strains from our laboratory. Genes encoding putative transcriptional regulator proteins and a catalase-like heme binding protein were found in C. coli genomes, but were absent in the genomes of C. jejuni. PCR screening showed the presence of a catalase-like protein gene in 75% (68/91) of C. coli strains, which was absent in all tested C. jejuni strains. While about 79% (30/38) of the hyper-aerotolerant C. coli strains harbored the catalase-like protein gene, the gene was also present in a number of the aerosensitive strains. The Catalase like protein gene was found to be expressed in both aerobic and microaerobic conditions with a two-fold higher gene expression detected in aerobic conditions for an aerosensitive strain. However, the exact function of the gene remains unclear and awaits further investigation. In conclusion, aerotolerant Campylobacter strains (especially C. coli) are prevalent in various retail meats. Further studies are needed to investigate whether the genes encoding catalase-like heme binding protein and putative transcriptional regulators in C. coli strains are involved in stress response and virulence mechanism.